Development of Riparian Plant Diversity Enrichment Book for Biology Student in Kampar Regency - Antika Gamiarsih; Yustina Yustina; Fitrah Suzanti (Journal of Educational Sciences, 2022)
This study aims to develop an enrichment book for Riparian plant species diversity in Kampar Regency. This research was carried out with an ADDIE development model consisting of the Analysis, Design, Development, Implementation and Evaluation stages. limited to the Development stage, namely the Validity Test due to time constraints. The type of data used is quantitative and qualitative data, the data sources are primary data and secondary data. The parameter in this study is the validity which is measured by using a Validation Questionnaire. Subject Experts who are competent in their fields. The results of the Material Expert Validation of the content feasibility component and the presentation of the material obtained an average score of 5 with a very good category. Media Experts for the Language component and Graphic Component obtained an average score of 5 in the very good category, the Biology teacher for the presentation of material/content, the language component, and the graphic component received an average score of 5 in the very good category. The conclusion of the book on Enrichment of Riparian Plant Species in Kampar Regency is the Valid and Eligible Category for use in the next stage.